Parent Experience of Hypoxic–Ischemic Encephalopathy and Hypothermia: A Call for Trauma Informed Care - Sagaser, Anna; Pilon, Betsy; Goeller, Annie; Lemmon, Monica; Craig, Alexa K. (American Journal of Perinatology, 2022)
Objective Therapeutic hypothermia (TH) is the standard treatment for hypoxic–ischemic encephalopathy (HIE). We surveyed parents of infants treated with TH about their experiences of communication and parental involvement in the neonatal intensive care unit (NICU).Study Design A 29-question anonymous survey was posted on a parent support (web site: https://www.hopeforhie.org) and sent to members via e-mail. Responses from open-ended questions were analyzed using thematic analysis.Results A total of 165 respondents completed the survey and 108 (66%) infants were treated with TH. 79 (48%) respondents were dissatisfied/neutral regarding the quality of communication in the NICU, whereas 127 (77%) were satisfied/greatly satisfied with the quality of parental involvement in the NICU. Six themes were identified as follows: (1) setting for communication: parents preferred face to face meetings with clinicians; (2) content and clarity of language: parents valued clear language (use of layman's terms) and being explicitly told the medical diagnosis of HIE; (3) immediate and longitudinal emotional support: parents required support from clinicians to process the trauma of the birth experience and hypothermia treatment; (4) clinician time and scheduling: parents valued the ability to join rounds and other major conversations about infant care; (5) valuing the parent role: parents desired being actively involved in rounds, care times, and decision-making; (6) physical presence and touch: parents valued being physically present and touching their baby; this presence was limited by the novel coronavirus disease 2019 (COVID-19)-related restrictions.Conclusion We highlight stakeholder views on parent involvement and parent–clinician communication in the NICU and note significant overlap with principles of trauma informed care: safety (physical and psychological), trustworthiness and transparency, peer support, collaboration and mutuality, empowerment, and voice and choice. We propose that a greater understanding and implementation of these principles may allow the medical team to more effectively communicate with and involve parents in the care of infants with HIE in the NICU.Key Points
Keywords: trauma-informed care; therapeutic hypothermia; hypoxic–ischemic encephalopathy; communication